The working principle and polarization curve of hydrogen trucks - Eshkobilova, Maftuna; Salomov, Uktam (MMIT Proceedings, 2025)
This research investigates the working principles and polarization curves of hydrogen fuel cells utilized in trucks, addressing the critical challenge of enhancing efficiency and performance under varying operational conditions. Through a comprehensive quantitative analysis, this study examines current-voltage characteristics, fuel cell temperature, and load conditions, revealing significant insights into the operational efficiencies of hydrogen trucks. The results indicate that optimized operational parameters can lead to substantial improvements in fuel cell performance, which is essential for promoting the adoption of hydrogen-powered vehicles in the logistics and transportation sectors. Moreover, the findings underscore the potential of hydrogen fuel cells to contribute to cleaner transportation solutions, which could have far-reaching implications for public health by reducing emissions and improving air quality. This research not only advances our understanding of hydrogen technology but also supports the broader objective of integrating sustainable energy solutions in transport, promoting a paradigm shift towards environmentally friendly options in healthcare logistics. The implications of this study extend to policymakers and industry stakeholders, presenting a pathway for the development of regulated standards and practices that enhance the reliability and sustainability of hydrogen fuel cell technology in commercial applications.